3D printed dual-functional biomaterial with self-assembly micro-nano surface and enriched nano argentum for antibacterial and bone regeneration. (December 2019) - Li, Jiayi; Li, Liangliang; Zhou, Jin; Zhou, Zhi; Wu, Xiao-ling; Wang, Liming; Yao, Qingqiang
Graphical abstract: Highlights: Scaffolds loaded with nano-silver showed better anti-infection property in vitro. Scaffold with large macroporosity and interconnected microstructure could provide a large amount of space for bone tissue ingrowth. The released AgNPs and PDA surface of scaffold may provide a bi-lineage conducive micro-environment for osteogenic differentiation and antibiosis at bone defect site. Abstract: Background: Infected bone defect (IBD) is still a great challenge in orthopaedic clinic. Scaffolds with dual-functional biological properties for antibacterial and bone regeneration may be a reasonable candidate for IBD repair. This study aims to develop a PCL/PDA/AgNPs scaffold with both antibacterial and bone regeneration ability for IBD repair. Materials and Methods: Porous polycaprolactone (PCL) scaffolds were prepared by 3D printing technology, with the enrichment of nano Argentum (nAg) achieved by modified bionic surface using self-assembly mussel-inspired polydopamine (PDA). The biomechanical strength, bone regeneration and anti-infection performance of the PCL/PDA/AgNPs scaffold, cultured in vitro and implanted in vivo, were examined to evaluate its suitability in infected bone repair. Results: Results demonstrated that the obtained PDA/PCL composite scaffolds and nAg/PDA/PCL composite scaffolds showed remarkable modification of surface with micro-nano self-assembly PDA and nAg particles observed, compared to PCL scaffold. No significant difference of scaffold density and compressive strength observed between composite scaffolds and PCL scaffolds. In vitro study showed that nAg/PDA/PCL scaffolds could decrease bacterial adhesion and reproduction. Meanwhile, nAg/PDA/PCL scaffolds showed a multiple action in the promotion of bone regeneration propriety by rBMSCs cell accommodation, attachment, proliferation. Furthermore, after 8 weeks of in vivo implantation, nAg/PDA/PCL scaffolds showed a superior performance in mineralized bone tissue accumulation, compared to PCL scaffolds. Conclusion: These findings suggest that PDA surface modification and drug enrichment can be a highly efficient and reliable method, which may improve the antibacterial and bone regeneration performance of 3D printed PCL scaffold. The nAg/PDA/PCL scaffold with bi-lineage bioactivity is a candidate for treating infected bone defect repair.